2017
DOI: 10.3847/1538-4357/aa6258
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Quiescence: The Dependence of Specific Star Formation Rate on Galaxy Size and Central Density at 0.5 < z < 2.5

Abstract: In this paper, we investigate the relationship between star formation and structure, using a mass-complete sample of 27,893 galaxies at 0.5<z<2.5 selected from 3D-HST. We confirm that star-forming galaxies are larger than quiescent galaxies at fixed stellar mass (M  ). However, in contrast with some simulations, there is only a weak relation between star formation rate (SFR) and size within the star-forming population: when dividing into quartiles based on residual offsets in SFR, we find that the sizes o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
138
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(162 citation statements)
references
References 113 publications
(214 reference statements)
24
138
0
Order By: Relevance
“…4 is inspired by Fig. 1 in Whitaker et al (2017) and shows very similar trends to the observations from the 3D-HST survey presented there. The full galaxy population (left column) shows a strong and continuous trend of decreasing sSFR with decreasing size, at a given stellar mass in the range 10 10−11 M .…”
Section: Comparison Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…4 is inspired by Fig. 1 in Whitaker et al (2017) and shows very similar trends to the observations from the 3D-HST survey presented there. The full galaxy population (left column) shows a strong and continuous trend of decreasing sSFR with decreasing size, at a given stellar mass in the range 10 10−11 M .…”
Section: Comparison Discussionmentioning
confidence: 52%
“…The value corresponding to the lower line, 266 km s −1 , is adopted from van Dokkum et al (2015) as the value where the quenched fraction is about 50% at 1.5 < z < 3. For lower redshifts, the values are scaled following Franx et al (2008), as galaxies at lower redshifts are found observationally to quench at lower velocity dispersions (or densities; see also Woo et al 2015;Whitaker et al 2017). This scaling leads to a value of 199 km s −1 at z = 1 and 168 km s −1 at z = 0.…”
Section: Comparison Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A dichotomy is also present in the sizemass relations, where quiescent galaxies exhibit a much steeper slope than SFGs and a lower normalization, i.e., higher densities (Williams et al 2010;Newman et al 2012;Shibuya et al 2015). Although both the SFR-MS and the size-mass scaling relations evolve with time, the fundamental structural differences in SFGs and quiescent galaxies are always present, suggesting that having concentrated (denser) surface density profiles is a requisite for quenching (Kauffmann et al 2003(Kauffmann et al , 2006Schiminovich et al 2007;Bell 2008;Cheung et al 2012;Fang et al 2013;Lang et al 2014;Abramson et al 2016;Margalef-Bentabol et al 2016;Whitaker et al 2017). In other words, SFGs must grow dense cores before quenching.…”
Section: Introductionmentioning
confidence: 99%
“…Here we study the evolution since z 3 of the stellar mass surface density within a radius of 1 kpc, 1 S . We build upon previous results at lower redshift, which show that 1 S is closely related with quiescence and follows a much tighter correlation with stellar mass than the effective radius or the effective surface density, e S (e.g., Cheung et al 2012;Fang et al 2013;Tacchella et al 2015;Woo et al 2015;Whitaker et al 2017). We aim to answer whether this relation holds at high redshift, if it is a more fundamental quenching predictor, and if the global build up and quenching of SFGs can be described in simple terms using 1 S , i.e., if it can be used to track galaxies in transit from the star-forming to the quiescent phase.…”
Section: Introductionmentioning
confidence: 99%